Implementasi Kurikulum yang Memberdayakan Konteks? - Arinta Kintan Larasati; Masduki Asbari; Putri Hafizhah Pinandita; Adhinta Darusancia Anggaini Putri (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to find out how the curriculum is implemented in the archipelago. As has been said, Indonesia has many islands and regions, so the implementation of the curriculum in each region is different. The need for education in developing an applicable curriculum, in order to improve the quality of human resources in the future. This study report uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to oral narratives from the YouTube channel Teacher Learning Stories entitled